Advanced Small Cell Lung Cancer with Cerebellar Metastases - A Case Report - Zhi Xiong Chong; Nazmi M. Noori (University Library System, University of Pittsburgh, 2015)
Background: Small cell lung cancer is an aggressive subtype of lung cancer whereby about one-third of cases are complicated with brain metastases. However, cerebellar metastases are uncommon and contribute to less than 10% of brain metastases. Case: We report a 76-year-old Malay male, an active smoker who presented with dyspnea and occasional cough with hemoptysis for one week. He also presented with headache and constitutional symptoms of malignancy. Clinical examination suggested the presence of right upper chest pathology and positive left cerebellar signs. His condition deteriorated two days later and he passed away after failed attempts at resuscitation. Chest radiograph showed right upper lobe collapse, and brain magnetic resonance imaging showed metastatic lesion in the left cerebellum extending to the right cerebellum. Post-mortem findings revealed small cell lung cancer with cerebellar metastases. Conclusion: Small cell lung cancer patients with brain metastases deteriorate very rapidly, and the management is mainly supportive. Primary prevention through education is the best way to reduce the incidence of lung cancer. In addition, secondary prevention and screening should be undertaken at earlier stages of the disease, as some studies have shown that combined chemotherapy and radiotherapy improve prognosis of malignancies detected at early stage.